Auditor Skill, Work Experience and Professional Skepticism on Performance of Auditors - Sunarmin Sunarmin; Ahmad Junaidi (Ilomata International Journal of Tax and Accounting, 2022)
Auditor is an accounting profession that is expected to be able to produce audit report products that can be accepted by both internal and external companies. The audit report must be existence and accuracy, completeness, rights and obligations, valuation or allocation, presentation and disclosure. To achieve this, several measuring tools are needed on how to determine the level of good auditor performance. The performance of professional auditors and having performance and broad insight will produce report products that can be accounted for and have reliable financial report functions and information. The research method used in this research is to use literature review, a systematic, explicit and reproducible method to identify, evaluate and synthesize research works and ideas that have been produced by researchers and practitioners. The results of this study can be concluded that good governance, audit structure, role conflict, role ambiguity, understanding of good governance, task complexity, have no effect on auditor performance. While organizational commitment, leadership style, professional training, competence, Locus of Control, and Auditor Integrity affect the performance of the auditor. For professional skepticism and audit knowledge, it turns out to have a positive and significant influence on the indications of regional loss findings.